Art Capital to Support the Establishment of Tourism Village of Tri Eka Buana Village in Sidemen, Karangasem - Sadguna, I Gde Agus Jaya; Sari, I Gusti Agung Mas Krisna Komala; Sudhana, I G.P. Fajar Pranadi (Journal of Business on Hospitality and Tourism, 2021)
The various potentials of each village or area in Bali has made it an island of prosperous wonders for tourism. Tri Eka Buana Village currently is in the process of becoming a tourism village, where Arak, a local liquor, is the main magnet. The aim of this research is 1) identify other aspects that support the development for the tourism village; 2) to identify the arts and cultures to be a capital that can support the development of the tourism village; 3) the attitude of the artists in the village towards the development of the tourism village. This research is a qualitative research, using purposive sampling to retrieve qualitative data from five determined interviewees, and uses the concept of tourism village and green tourism as the applicative theory. The result shows that, 1). although Tri Eka Buana Village’s main magnet is arak, arts and culture reside together in the village as an important aspect for the establishment of the tourism village; 2). this village has several forms of arts and culture such as Utamaning Malini Dance, Jaga-jaga Dance, pesantian, drama gong (theater), and traditional dances that are commonly used as entertainment; and 3).the artists in this village is willing to support the establishment of the tourism village by creating new dances and performances that are more suitable to showcase to future tourists.